Living with disasters: social capital for disaster governance. Issue 3 (24th October 2017) - Melo Zurita, Maria de Lourdes; Cook, Brian; Thomsen, Dana C.; Munro, Paul G.; Smith, Timothy F.; Gallina, John
Abstract : This paper explores how social networks and bonds within and across organisations shape disaster operations and strategies. Local government disaster training exercises serve as a window through which to view these relations, and 'social capital' is used as an analytic for making sense of the human relations at the core of disaster management operations. These elements help to expose and substantiate the often intangible relations that compose the culture that exists, and that is shaped by preparations for disasters. The study reveals how this social capital has been generated through personal interactions, which are shared among disaster managers across different organisations and across 'levels' within those organisations. Recognition of these 'group resources' has significant implications for disaster management in which conducive social relations have become paramount. The paper concludes that socio‐cultural relations, as well as a people‐centred approach to preparations, appear to be effective means of readying for, and ultimately responding to, disasters.